Dynamic Measurement of Hemodynamic Parameters and Cardiac Preload in Adults with Dengue: A Prospective Observational Study. - Vipa Thanachartwet; Anan Wattanathum; Duangjai Sahassananda; Petch Wacharasint; Supat Chamnanchanunt; Ei Khine Kyaw; Akanitt Jittmittraphap; Mali Naksomphun; Manoon Surabotsophon; Varunee Desakorn (PLoS ONE)
Few previous studies have monitored hemodynamic parameters to determine the physiological process of dengue or examined inferior vena cava (IVC) parameters to assess cardiac preload during the clinical phase of dengue. From January 2013 to July 2015, we prospectively studied 162 hospitalized adults with confirmed dengue viral infection using non-invasive cardiac output monitoring and bedside ultrasonography to determine changes in hemodynamic and IVC parameters and identify the types of circulatory shock that occur in patients with dengue. Of 162 patients with dengue, 17 (10.5%) experienced dengue shock and 145 (89.5%) did not. In patients with shock, the mean arterial pressure was significantly lower on day 6 after fever onset (P = 0.045) and the pulse pressure was significantly lower between days 4 and 7 (P<0.05). The stroke volume index and cardiac index were significantly decreased between days 4 and 15 and between days 5 and 8 after fever onset (P<0.05), respectively. A significant proportion of patients with dengue shock had an IVC diameter <1.5 cm and IVC collapsibility index >50% between days 4 and 5 (P<0.05). Hypovolemic shock was observed in 9 (52.9%) patients and cardiogenic shock in 8 (47.1%), with a median (interquartile range) time to shock onset of 6.0 (5.0-6.5) days after fever onset, which was the median day of defervescence. Intravascular hypovolemia occurred before defervescence, whereas myocardial dysfunction occurred on the day of defervescence until 2 weeks after fever onset. Hypovolemic shock and cardiogenic shock each occurred in approximately half of the patients with dengue shock. Therefore, dynamic measures to estimate changes in hemodynamic parameters and preload should be monitored to ensure adequate fluid therapy among patients with dengue, particularly patients with dengue shock.